2019
DOI: 10.1039/c8ra10304f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of κ2-N,O-oxazoline-enolate complexes of nickel(ii): explorations in coordination chemistry and metal-mediated polymerisation

Abstract: The synthesis and characterisation (UV-Vis, IR, X-ray diffraction, etc.) of a series of Ni(II) complexes derived from both known and novel 2-acylmethyl-2-oxazolines (2a-g: i.e., (Z)-1-R-2-(4,4 0 -dimethyl-2 0 -oxazolin-These Ni materials (3a-g) represent the first group 10 metal complexes of this ligand class. All derivativesen-1-ate formed via proton loss from 2. The air-and moisture-stable metal complexes feature a less typical distorted seesaw-shaped disposition of binding atoms around the metal centre for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 145 publications
0
12
0
Order By: Relevance
“…[19][20][21] Other examples include those by Gossage and Baruah where homoleptic complexes of Ni(II) were synthesized with bulky propan-2-ylidene and oxazoline substituents that prevent planarization of the Ni(II) coordination environment. 14,22 Another recent example of a seesaw geometry at a Ni(II) center involves a diisopropylpyrazole-substituted carbazole ligand to enforce steric crowding of the square plane. 13 Finally, an example of a ligand-constrained geometry around a Ni(II) center can be seen in a complex bound to a triphosphacyclododecane ligand.…”
mentioning
confidence: 99%
“…[19][20][21] Other examples include those by Gossage and Baruah where homoleptic complexes of Ni(II) were synthesized with bulky propan-2-ylidene and oxazoline substituents that prevent planarization of the Ni(II) coordination environment. 14,22 Another recent example of a seesaw geometry at a Ni(II) center involves a diisopropylpyrazole-substituted carbazole ligand to enforce steric crowding of the square plane. 13 Finally, an example of a ligand-constrained geometry around a Ni(II) center can be seen in a complex bound to a triphosphacyclododecane ligand.…”
mentioning
confidence: 99%
“…Previous work on Ni(II) systems had revealed that coordination is facilitated by the addition of base to a Ni(II) salt; hence, we employed a similar tactic here. [45] Thus, treatment of solutions (EtOH / MeOH) of cobaltous chloride or nitrate with 1a -1c, in the presence of excess of NEt3, were found to be optimal to give the corresponding Co(1 -H)2 complexes (2a -2c: Scheme 2 and Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
“…Such a situation we have already probed in the chemistry of four-coordinate Ni(II). [45] These Group 10 compounds likewise reveal uncommon bonding modes at the Ni centres. In addition, these materials have been shown to be useful polymerization catalysts when employing alkyl Al reagents as co-promoters.…”
Section: Introductionmentioning
confidence: 97%